Treatment of Symptomatic Lymphedema in the Hand with Omental Flow-through Flap - Peaches A. Dozier, BA; Adam J. Reid, MD, FACS; Brian A. Mailey, MD, FACS (Plastic and Reconstructive Surgery, Global Open, 2023)
Summary:. Vascularized lymph node transfer (VLNT) is a surgical option to improve physiologic lymphatic drainage. This technique transfers healthy vascularized lymphatic tissue from various available donor sites to the existing lymphatics of the affected area. Here, we present a successful case halting the size progression and reversing lymphedema symptoms in a patient treated with vascularized omental lymph node transfer. A 56-year-old man presented with stage III malignant sarcoma of his left medial upper arm. Two-years after excision, flap reconstruction, and radiation brachytherapy, worsening diffuse left arm edema developed, causing pain, decreased range of motion, and paresthesia. A vascularized omental lymph node transfer was performed. The omental flap required a flow-through design, requiring anastomosis of both gastroepiploic arteries to obtain Dopplerable signals. The patient experienced progressive relief of lymphedema symptoms after this transfer. Treatment outcomes with the use of VLNT have been largely encouraging; however, objective measures of improvement and timing of neolymphangiogenesis in recipient lymph node sites still need to be defined. Understanding omental VLNT flow dynamics and expected time point changes during the postoperative course will define expected outcomes and allow for treatment of a greater number of patients affected by lymphedema.